Role of Brain Arterial Remodeling in HIV-Associated Cerebrovascular Outcomes - Spagnolo-Allende, Antonio; Gutierrez, Jose (Frontiers in Neurology, 2021)
As the life expectancy of people living with HIV (PLWH) on combination antiretroviral therapy (cART) increases, so does morbidity from cerebrovascular disease and neurocognitive disorders. Brain arterial remodeling stands out as a novel investigational target to understand the role of HIV in cerebrovascular and neurocognitive outcomes. We therefore conducted a review of publications in PubMed, EMBASE, Web of Science and Wiley Online Library, from inception to December 2020. We included search terms such as HIV, cART, brain, neuroimmunity, arterial remodeling, cerebrovascular disease, and neurocognitive disorders. The literature shows that, in the post-cART era, PLWH continue to experience an increased risk of stroke and neurocognitive disorders (albeit milder forms) compared to uninfected populations. PLWH who are immunosuppressed have a higher proportion of hemorrhagic strokes and strokes caused by opportunistic infection and HIV vasculopathy, while PLWH on long-term cART have higher rates of ischemic strokes, compared to HIV-negative controls. Brain large artery atherosclerosis in PLWH is associated with lower CD4 nadir and higher CD4 count during the stroke event. HIV vasculopathy, a form of non-atherosclerotic outward remodeling, on the other hand, is associated with protracted immunosuppression. HIV vasculopathy was also linked to a thinner media layer and increased adventitial macrophages, suggestive of non-atherosclerotic degeneration of the brain arterial wall in the setting of chronic central nervous system inflammation. Cerebrovascular architecture seems to be differentially affected by HIV infection in successfully treated versus immunosuppressed PLWH. Brain large artery atherosclerosis is prevalent even with long-term immune reconstitution post-cART. HIV-associated changes in brain arterial walls may also relate to higher rates of HIV-associated neurocognitive disorders, although milder forms are more prevalent in the post-cART era. The underlying mechanisms of HIV-associated pathological arterial remodeling remain poorly understood, but a role has been proposed for chronic HIV-associated inflammation with increased burden on the vasculature. Neuroimaging may come to play a role in assessing brain arterial remodeling and stratifying cerebrovascular risk, but the data remains inconclusive. An improved understanding of the different phenotypes of brain arterial remodeling associated with HIV may reveal opportunities to reduce rates of cerebrovascular disease in the aging population of PLWH on cART.